A Comparative Analysis of Embedding Responsible Innovation in Integrated Engineering Curricula: A Case Study of Established vs Emerging Universities - Ramachandran, Vivek; Shinde, Rhythima; Tilley, Emanuela (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
As engineering education evolves to meet the demands of an increasingly complex world, especially in times of a climate crisis, universities must prepare students to develop technologies that are ethical, sustainable, and socially responsible. Responsible Innovation provides a framework for achieving this by integrating ethics, sustainability, risk mitigation, and equity, diversity, and inclusion into engineering curricula. Engineers have long influenced society through innovation, acting as agents of change. Given the lasting impact of engineering decisions, future engineers must be equipped to anticipate risks, uphold ethical standards, and design inclusive solutions that serve diverse communities. Many institutions are shifting toward integrated education models that emphasise real-world applications through project-based learning (PjBL). This paper compares how RI is embedded within two academic frameworks: (a) the established Integrated Engineering Programme at University College London (UCL), an interdisciplinary approach that works within that a discipline-based departmental structure (e.g., mechanical, electrical, chemical engineering) by combining project- and lecture-based learning, and (b) the Interdisciplinary Global Design Engineering Programme at emerging institutions like The Engineering & Design Institute London (TEDI-London), which employs a fully project-based learning approach. By examining these programmes, through an auto-ethnographic study, by interviewing two early-career academics from these institutions, capturing their reflections on the challenges and opportunities of embedding RI in engineering curricula. Ultimately, this paper offers recommendations for strengthening the integration of RI within engineering curricula, tailored to each programme’s unique characteristics. It contributes to ongoing discourse on preparing engineers to navigate global challenges, emphasising inter- and trans-disciplinary competencies as essential for future demands.